The Multiple Biological Functions of Dipeptidyl Peptidase-4 in Bone Metabolism - Yang, Qiu; Fu, Bing; Luo, Dan; Wang, Haibo; Cao, Hongyi; Chen, Xiang; Tian, Li; Yu, Xijie (Frontiers in Endocrinology, 2022)
Dipeptidyl peptidase 4 (DPP4) is a ubiquitously occurring protease involved in various physiological and pathological processes ranging from glucose homeostasis, immunoregulation, inflammation to tumorigenesis. Recently, the benefits of DPP4 inhibitors as novel hypoglycemic agents on bone metabolism have attracted extensive attraction in many studies, indicating that DPP4 inhibitors may regulate bone homeostasis. The effects of DPP4 on bone metabolism is still unclear. This paper thoroughly reviews the potential mechanisms of DPP4 for interaction with adipokines, bone cells, bone immune cells, and cytokines in skeleton system. This literature review shows that the increased DPP4 activity may indirectly promote bone resorption and inhibit bone formation, increasing the risk of osteoporosis. Thus, bone metabolic balance can be improved by decreasing DPP4 activities. The substantial evidence collected and analyzed in this review supports this implication.